Mutations in KRT10 in epidermolytic acanthoma. - Cheraghlou, Shayan; Atzmony, Lihi; Roy, Simon F; McNiff, Jennifer M; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Epidermolytic acanthoma (EA) is a rare acquired lesion demonstrating a characteristic histopathological pattern of epidermal degeneration referred to as epidermolytic hyperkeratosis (EHK). On histopathological analysis, EA appears nearly identical to inherited EHK-associated dermatoses such as epidermolytic ichthyosis and ichthyosis bullosa of Siemens. While it has been speculated that EA is caused by mutations in KRT10, KRT1, or KRT2 found in these inherited dermatoses, none have yet been identified. Herein, we aim to identify the contributions of keratin mutations to EA. METHODS: Using genomic DNA extracted from paraffin-embedded samples from departmental archives, we evaluated a discovery cohort using whole-exome sequencing (WES) and assessed remaining samples using Sanger sequencing screening and restriction fragment length polymorphism (RFLP) analysis. RESULTS: DNA from 16/20 cases in our sample was of sufficient quality for polymerase chain reaction amplification. WES of genomic DNA from lesional tissue revealed KRT10 c.466C > T, p.Arg156Cys mutations in 2/3 samples submitted for examination. RFLP analysis of these samples as well as eight additional samples confirmed the mutations identified via WES and identified four additional cases with Arg156 mutations. In sum, 6/11 screened cases showed hotspot mutation in KRT10. CONCLUSIONS: Hotspot mutations in the Arg156 position of KRT10, known to cause epidermolytic ichthyosis, also underlie EA.
Keywords: Acanthoma; Adult; Aged; Aged, 80 and over; Female; Genomics; Humans; Hyperkeratosis, Epidermolytic; Ichthyosis Bullosa of Siemens; Keratin-10; Keratins; Male; Middle Aged; Mutation; Skin Neoplasms; Whole Exome Sequencing

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Somatic V600E BRAF Mutation in Linear and Sporadic Syringocystadenoma Papilliferum. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; Bilguvar, Kaya; McNiff, Jennifer M; Choate, Keith A (J Invest Dermatol, 2015)
Keywords: Biopsy, Needle; Child; Cystadenoma; Female; Gene Expression Regulation, Neoplastic; Humans; Immunohistochemistry; Mutation; Proto-Oncogene Proteins B-raf; Sweat Gland Neoplasms; Syringoma

Somatic HRAS p.G12S mutation causes woolly hair and epidermal nevi. - Levinsohn, Jonathan L; Teng, Joyce; Craiglow, Brittany G; Loring, Erin C; Burrow, T Andrew; Mane, Shrikant S; Overton, John D; Lifton, Richard P; McNiff, Jennifer M; Lucky, Anne W; Choate, Keith A (J Invest Dermatol, 2014)
Keywords: Adherens Junctions; Child; Exome; Female; Genes, ras; Hair; Hair Diseases; Hair Follicle; Humans; Intermediate Filaments; Mosaicism; Mutation; Nevus; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction

Whole-exome sequencing reveals somatic mutations in HRAS and KRAS, which cause nevus sebaceus. - Levinsohn, Jonathan L; Tian, Li C; Boyden, Lynn M; McNiff, Jennifer M; Narayan, Deepak; Loring, Erin S; Yun, Duri; Sugarman, Jeffrey L; Overton, John D; Mane, Shrikant M; Lifton, Richard P; Paller, Amy S; et al. (J Invest Dermatol, 2013)
Keywords: Adolescent; Adult; Amino Acid Sequence; Biopsy; Child; Child, Preschool; Cohort Studies; Epidermis; Exome; Humans; Infant; Middle Aged; Molecular Sequence Data; Mutation; Nevus, Sebaceous of Jadassohn; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; Sequence Analysis, DNA; Young Adult